The Drake Equation - King, Bart, 1962- (Disney Hyperion, 2016)
"Noah Grow is a birdwatcher who is on a quest to find a Wood Duck, but instead finds a strange, bedazzled disc. Noah and his best friends, Jason and Jenny, soon discover that the mysterious disc gives Noah peculiar powers. As things go from odd to outrageous, Noah is swept up in a storm of intergalactic intrigue and middle school mayhem"--Provided by publisher.